Advantages of application of unconventional computing to image processing and whence these advances come - Lyudmila Burtseva (Computer Science Journal of Moldova, 2016)
This paper presents the advantages of P system computing based approach to solving image processing problems. Being significantly reduced relative to classic algorithms, P system computing based algorithms nevertheless produce better results and even resolve the problems just unsolvable for classic algorithms. Despite these evident advances, unconventional computing approaches remain less popular in practical image processing because their hardware is mostly “virtual” that supposes computing on simulator. This obstacle can be in perspective eliminated by direct implementation of P system computing based solutions on today's HPC hardware.